Залежність чисельності гетеротрофних джгутикових центральної частини Українського Полісся від абіотичних факторів водного середовища - Шевчук, Світлана; Васільєва, Людмила; Shevchuk, Svitlana; Vasilieva, Lyudmylа (Східноєвропейський національний університет імені Лесі Українки, 2015)
Досліджено залежність чисельності гетеротрофних джгутикових центральної частини Українського Полісся від активної реакції водного середовища, умісту розчинених у воді кисню та органічних речовин. Установлено, що чисельність P. nitrophilus залежить від рН і розчинених у воді органічних речовин, A. tachyploon, B. globosus, G. truncata, P. apiculatus, R. nasuta – від розчиненого у воді кисню, а A. sigmoides, B. saltans, P. simplex – від розчинених у воді органічних речовин. We studied the dependence of heterotrophic flagellate numbers on the several hydrochemical parameters (pH, maintenance solubility in water oxygen and organic substances). This dependence was examined using one-way ANOVA. For species Allantion tachyploon Sandon, 1924, Bodo globosus Stein, 1878, Goniomonas truncata (Fresenius) Stein, 1887, Phyllomitus apiculatus Skuja, 1948 and Rhynchomonas nasuta (Stokes, 1888) Klebs, 1892 the reliable connection between the quantity and the maintenance solubility in water oxygen was determined, whereas in Ancyromonas sigmoides Kent, 1880, Bodo saltans Ehrenberg, 1832, Parabodo nitrophilus Skuja, 1948 and Protaspis simplex Vǿrs, 1992 the influence of maintenance solubility in water organic substances was significant. Furthermore in Parabodo nitrophilus Skuja, 1948 the pH value appreciably affect the species number.
Dependence of Heterotrophic Flagellates Central Part of Ukrainian Polissia Area Abundance on the Abiotic Factors Water Environment.
Keywords: гетеротрофні джгутикові; Українське Полісся; абіотичні фактори водного середовища; heterotrophic flagellates; Ukrainian Polissia; abiotic factors water environment